SPE Reservoir Simulation Conference 2019
DOI: 10.2118/193827-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Embedded Discrete Fracture Modeling Workflow for Simulating Complex Processes in Field-Scale Fractured Reservoirs

Abstract: Traditionally, fractured reservoir simulations use Dual-Porosity, Dual-Permeability (DPDK) models that can idealize fractures and misrepresent connectivity. The Embedded Discrete Fracture Modeling (EDFM) approach improves flow predictions by integrating a realistic fracture network grid within a structured matrix grid. However, small fracture cells with high conductivity that pose a challenge for simulators can arise and ad hoc strategies to remove them can alter connectivity or fail for field-scale cases. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This method is explained in more detail and used to model flow in unconventional oil and gas reservoirs in Chapter 10. Hui et al [18] have further simplified and optimized the EDFM preprocessing algorithm, thus allowing users to handle a much larger number of fractures. Additionally, various authors have coupled EDFM with geomechanical simulations for fully coupled simulations [35,38,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is explained in more detail and used to model flow in unconventional oil and gas reservoirs in Chapter 10. Hui et al [18] have further simplified and optimized the EDFM preprocessing algorithm, thus allowing users to handle a much larger number of fractures. Additionally, various authors have coupled EDFM with geomechanical simulations for fully coupled simulations [35,38,50].…”
Section: Discussionmentioning
confidence: 99%
“…Vo et al [45] compared DFM and dual-permeability models and identified a range of deficiencies in terms of the dual-permeability method's ability to account for viscous displacement and spontaneous imbibition. Hui et al [18] used a DFM method to simulate waterflooding in a full-field model in which the fracture network is simplified via a method known as edge collapse. In this simplification, short fracture segments with hanging nodes are removed to reduce the degrees of freedom involved in the simulations.…”
Section: Introductionmentioning
confidence: 99%
“…These nine DFNs are intended to 'span' the range of uncertainty in the spatial variability and connectivity of the fracture system. Please see [16] for a more detailed description of the workflow used to grid and simulate the ensemble of EDFMs.…”
Section: Fractured Model Setupmentioning
confidence: 99%
“…The field has over 10 years of primary production history, and a multiyear waterflood pilot involving two injectors with tracers is currently being planned to evaluate water injection as a potential full-field improved oil recovery (IOR) strategy. In this study, a large set of prior models (1850) is generated and simulated using an efficient workflow [16]. These models are based on nine discrete fracture network realizations and a range of matrix and fracture parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation